An Investigation Study of Tool Geometry in Single Point Incremental Forming (SPIF) and their effect on Residual Stresses Using ANOVA Model - Aqeel S Sabree Bedan (Al-Khwarizmi College of Engineering – University of Baghdad, 2019)
Incremental forming is a flexible sheet metal forming process which is performed by utilizing simple tools to locally deform a sheet of metal along a predefined tool path without using of dies. This work presents the single point incremental forming process for producing pyramid geometry and studies the effect of tool geometry, tool diameter, and spindle speed on the residual stresses. The residual stresses were measured by ORIONRKS 6000 test measuring instrument. This instrument was used with four angles of (0º,15º,30º, and 45º) and the average value of residual stresses was determined, the value of the residual stress in the original blanks was (10.626 MPa). The X-ray diffraction technology was used to measure the residual stresses. The sheet material used was Aluminum alloy (AL1050) with thickness of (0.9 mm). The experimental tests in this work were done on the computer numerical control (CNC) vertical milling machine. The extracted results from the single point incremental forming process were analyzed using analysis of variance (ANOVA) to predict the effect of forming parameters on the residual stresses. The optimum value of the residual stresses (55.024 MPa) was found when using the flat end with round corner tool and radius of (3 mm), wall angle of (55°) and a rotational speed of the tool of (800 rpm). The minimum value of the residual stresses (24.389MPa) was found when using hemispherical tool with diameter of (12 mm), wall angle of (45°) and a rotational speed of the tool of (800 rpm).